Are Corneal Patients Accepting the Transplantation? The Cases of University of Gondar, Tertiary Eye Care and Training Center, Ethiopia. (13th December 2019) - Jemberu, Yordanos Tsehai; Woldie, Yared Assefa; Mulugeta, Wossen; Shiferaw Alemu, Destaye; Bantie, Getasew Mulat
Abstract : Background . For so long, corneal diseases have been known as one of the leading causes to blindness in the global. This blindness might be due to failure to accept the corneal transplantation. Therefore, this study aimed to determine the prevalence and the root challenges for corneal transplantation acceptance at the University of Gondar tertiary eye care and training center, Ethiopia. Methods . An institution-based cross-sectional study was conducted among patients who had an indication for corneal transplantation at the University of Gondar tertiary eye care and training center since January 1, 2017, up to October 30, 2018. A structured questionnaire was used to collect the data and entered into Epi-Info 7 software and analyzed using SPSS version 20. Simple logistic regression was used to identify the associated factors of corneal transplantation acceptance. Associations between outcome and exposure variables were expressed by the adjusted odds ratio with a 95% confidence interval and p value <0.05. Result . A total of 116 patients with a mean age of 51 (±21) years participated in the study. The overall acceptance level of corneal transplantation was only 38.8% (95% CI: 29.93, 47.66). Patients with poor knowledge [AOR = 2.41; 95% CI: 1.90, 6.48] and an unfavorable attitude [AOR = 6.33; 95% CI: 2.42, 16.54] were significantly associated with the acceptance of corneal transplantation. Conclusion . The study revealed that the corneal transplantation acceptance level was very low. Hence, the government and other concerned stakeholders should give due emphasis to the awareness creation and behavior change communication strategies to increase the acceptance level of corneal transplantation.